Reactive oxygen species–post translational modifications–central carbon metabolism regulatory loop: coordination of redox homeostasis and carbon flux allocation in plants under abiotic stress - Bao, Linfeng; Wang, Wenya; Li, Mengyang; Liu, Jie; Liu, Jiahao; Alifu, Gulizhare; Wang, Desheng; Liang, Xueqi; Mao, Tingyong; Zhai, Yunlong (Frontiers in Plant Science, 2025)
Reactive oxygen species (ROS) play dual roles in plants as signaling molecules and cytotoxic agents, making ROS homeostasis critical for abiotic stress adaptation. Numerous studies have shown that central carbon metabolism (CCM) provides the energy required for plant growth and maintains ROS homeostasis by coordinating energy distribution and reconfiguring metabolic streams under abiotic stress, providing energy and metabolites for plants to resist adverse conditions. As a crucial mechanism by which cells respond to short-term stress, post-translational modifications (PTMs) influence CCM by targeting and modifying its enzymes. This enables both energy and metabolic flow redistribution, enabling plants to balance growth and defense under stress conditions. In this review, we discuss the ROS–PTM–CCM interaction and how it improves plant adaptation to abiotic stress. We propose that ROS coordinate ROS homeostasis by mediating the feedback regulation of CCM through PTMs under abiotic stress. This review provides a theoretical basis for improving crop stress tolerance through PTM-targeted metabolic engineering.